Residue curve maps of 4-component systems. Poincare index determination for 4-component azeotrope - L. A. Serafimov; A. V. Frolkova; D. V. Medvedev; G. A. Semin (Тонкие химические технологии)
A method of Poincare index determination for a singular point corresponding to a 4-component azeotrope is proposed. The method is based on the equation of azeotropic relationship. 2-Dimensional diagram covering the 3-dimensional residue curve map as a surface is meant to be given originally.